Germination behaviour of four mediterranean Cistus L. species in relation to high temperature - Scuderi, Domenica; Di Gregorio, Rosa; Toscano, Stefania; Cassaniti, Carla; Romano, Daniela (Ecological Questions, 2010)
Cistus is one of the most characteristic genera of the Mediterranean flora. These species, natives of lands surrounding the Mediterranean Sea, are present in scrubland and garigue on siliceous ground and often on acid soil; seven species in particular are founded in Sicily. The adaptation of the genus to Mediterranean environments is evident from ecological characteristics such as fire-dependent seed germination; the heat generated by fire is in fact a key germination input. In this view, two experiments were performed to study the effects of high temperature on germination of four Cistus species (C. creticus L., C. crispus L., C. monspeliensis L., C. salviifolius L.). In the first, in relation to untreated control, 7 different high temperature pre-treatments (from 70°C to 130°C) for different timings (from 1 to 10 minutes) were analysed in relation to two sowing strategies (soon after the seed collection and after a 6 month period at 5°C to simulate the winter season effects). The pre-treatment with high temperatures can improve the germination; the storage at 5°C to simulate the winter season effects did not modify the germination process. In any case the results showed a species-dependent response. High germination percentage was obtained for C. creticus, while a lower germination rate was achieved by C. crispus and C. monspeliensis. In the second experiment, seeds were treated for different periods (80°C for 10 min, 90°C for 5 min and 100°C for 1 min) with high temperature in dry and wet (immersion in distilled water) conditions. Also in this case the responses were strictly linked to the species. Especially C. crispus and C. monspeliensis showed high germination percentage in wet conditions. In all species the wet heat treatments determined an accelerating of process like demonstrated by lower T50 values.